Solute clusters-promoted strength-ductility synergy in Al-Sc alloy. (10th January 2022) - Yang, Chong; Cheng, Pengming; Chen, Baoan; Zhang, Jinyu; Liu, Gang; Sun, Jun
Highlights: Sc clusters with a high number density were produced in Al-Sc alloy aged at 250 °C. The evolution of Sc clusters with aging time was characterized by APT. The Sc solute cluster could promote strength-ductility synergy in Al-Sc alloy. The effect of clusters on ductility is discussed by a revised micromechanics model. Abstract: Sc solute clusters with a high number density were produced in an Al-0.3 wt.% Sc alloy when aged at 250 °C, while fine Al3 Sc precipitates were predominantly formed in the same alloy aged at 300 °C. The alloy strengthened by Sc solute clusters displayed higher yield strength and simultaneously greater ductility than its counterpart strengthened by Al3 Sc precipitates. This clearly demonstrates a superior strength-ductility synergy promoted by the Sc solute clusters in Al-Sc alloys. The effects of Al3 Sc precipitates and Sc solute clusters on ductility were discussed in comparison by using a micromechanics fracture model. Since the Sc clusters were stabilized at 250 °C, the Al-Sc alloys strengthened by Sc solute clusters should find extensive application fields within a wide temperature range, due to their high temperature resistance. Graphical abstract: Image, graphical abstract